Fifty years after Popular Unity: Chile's estallido social in historical context. (1st June 2021) - Frens-String, Joshua; Harmer, Tanya; Schlotterbeck, Marian
Abstract : In this article, the co-editors introduce key themes and contributions of this special issue of Radical Americas, particularly as they pertain to the 50th anniversary of Chile's Popular Unity revolution (1970–3) and the more recent estallido social (social uprising), which began in Santiago de Chile in October 2019. They underline the historical context for contemporary events, arguing the need to recognise the influence, memory and significance of the past in the present.